Identification of the base of the lower-to-middle Campanian Globotruncana ventricosa Zone: comments on reliability and global correlations - M. R. Petrizzo; F. Falzoni; I. Premoli Silva (Cretaceous Research, 2011)
The reliability of the first appearance datum of Globotruncana ventricosa as biozonal marker for the Campanian is discussed. The taxonomy and species concept of G. ventricosa and of Globotruncana tricarinata, that has been either regarded as junior synonym of Globotruncana linneiana or of G. ventricosa, are examined to avoid misidentifications, and one species is here formally described as new, Globotruncana neotricarinata nov. sp. The tropical and subtropical planktic foraminiferal assemblages from the Bottaccione section (Gubbio, Italy), from Deep Sea Drillig Project (DSDP) Site 146 (Caribbean Sea, central Atlantic Ocean), and from Ocean Drilling Program (ODP) Hole 1210B (Shatsky Rise, northwestern Pacific Ocean) are analyzed for the presence of biostratigraphic markers. Lowest and highest occurrence data have been checked in thin sections and washed residues in the Bottaccione section. The comparative biostratigraphic analysis of the planktic foraminiferal distribution highlights: 1) the absence of G. ventricosa at the stratigraphic level at which it is supposed to first occur in the Tethyan area, 2) the presence of transitional specimens resembling G. ventricosa and thus erroneously used to identify the base of the G. ventricosa Zone, 3) the presence of a good sequence of bioevents that appear to be promising for regional and global correlations such as the appearance of Globotruncanita atlantica, Contusotruncana plummerae and the disappearance of Hendersonites carinatus. The correlation potential of these bioevents has been verified across latitudes by studying the Campanian planktic foraminiferal assemblage in pelagic sediments drilled on coastal Tanzania (western Indian Ocean), and at the deep-sea ODP Hole 762C (Exmouth Plateau, western Indian Ocean), that were located at 30°S and 47°S in the Late Cretaceous, respectively. Besides the known diachronous first appearance of G. ventricosa in the Southern Ocean sites, results confirm the difficulty in using G. ventricosa as zonal marker in the tropical and ...